Ni-Doped ZrO2 nanoparticles decorated MW-CNT nanocomposite for the highly sensitive electrochemical detection of 5-amino salicylic acid. Issue 2 (18th November 2020) - Nataraj, Nandini; Krishnan, Siva Kumar; Chen, Tse-Wei; Chen, Shen-Ming; Lou, Bih-Show
Abstract : Ni-ZrO2 /MWCNT/GCE for highly sensitive electrochemical detection of 5-ASA in biofluids. Abstract : In this work, Ni-doped ZrO2 nanoparticles (NPs) were used to decorate multi-walled carbon nanotubes (MWCNTs) to obtain a Ni-ZrO2 /MWCNT nanocomposite, which acted as an efficient electrode material for the highly sensitive electrochemical detection of the anti-inflammatory drug 5-amino salicylic acid (5-ASA). The Ni-ZrO2 NPs were obtained through a facile co-precipitation method, and the subsequent support of these Ni-ZrO2 NPs onto MWCNTs was accomplished via an ultrasonication technique. Supporting Ni-ZrO2 NPs on MWCNTs not only results in excellent catalytic properties, but it also substantially enhances the surface area, electrical conductivity, and electron transfer process. The electrochemical activity of the synthesized Ni-ZrO2 /MWCNT nanocomposite was systematically investigated via cyclic voltammetry (CV) and differential pulse voltammetry (DPV) techniques. The constructed Ni-ZrO2 /MWCNT-modified glassy carbon (GC) electrode manifests superior electrocatalytic oxidation activity toward 5-ASA, with a lower peak potential compared with Ni-ZrO2 -NP- and MWCNT-modified GC electrodes. Importantly, the proposed biosensor exhibited excellent sensitivity during the detection of 5-ASA with a wide linear concentration range (0.001–500 μM) and a low detection limit of 0.0029 μM. Moreover, the biosensor demonstrated excellent repeatability, reproducibility, stability, and high specificity toward 5-ASA detection in the presence of different interfering species. Furthermore, the biosensor showed satisfactory recovery rates in complex biological samples, such as human blood serum, human urine, and 5-ASA tablet samples.